Praktik Dumping (Siyasah Al-Ighraq); Pandangan Imam Suyuthi Perspektif Ekonomi Islam - Thoha Yasin Utsman; Syamsul Ma’arif (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
The practice of Islamic economics during the time of Rasulullah SAW, the generation of companions (khulafa ar-rasyidun), and afterward played a significant role in the development of prosperity and social justice. Furthermore, every adherent is required to apply fiqh law in the development of the Islamic economy. However, in today's world, trading practices have spread to international networks, resulting in dumping. Dumping is the practice of exporters selling products at relatively lower prices than normal prices. The goal of this research is to discover why Imam Suyuthi believes that dumping (siyasah al-ighraq) in trade is permissible. Although Imam Suyuthi, the founder of the leading Syafi'iyah school in 9th century Hijriyah, did not specifically discuss dumping law, he did explain various fiqh principles (Qaidat al-Fiqh) in his work Al-Asybah Wa An-Nadzair, so that he could reformulate every event that has not and will not appear in classical fiqh problems. The authors are well aware that the term dumping (Siyasat al-ighraq) was not found during the time of Rasulullah SAW, so Islamic law researchers linked the policy of Amir al-Mukminin, Caliph Umar bin Khatab RA.. This is library research (Library research), and the authors use a qualitative research method, which is a type of research in which data is obtained from documentation data, such as books, laws, and so on. In terms of analyzing the constituent data using analytical descriptive analysis, the goal is to describe and analyze the data in depth. While the approach model employed is historical and social in nature. Imam Suyuthi's viewpoint on the practice of dumping in trade, citing the need to eliminate harm and the importance of government policies in meeting the needs of its citizens. Imam Khawarizmi proposed